APLIKASI PENDATAAN PENCARI KERJA DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN MANGGARAI TIMUR BERBASIS WEBSITE - Fransiskus Zaverius Ganggur; yohanis malelak (JITU : Journal Informatic Technology And Communication, 2019)
Programming through computer technology in this day a rapid growth experience. This shows a tendency that led to the creation and development of an automated technology means a more practical, efficient and economical to facilitate and accelerate all human activity. The spread of information technology, which is less than optimal and uneven, felt weakness in the agency's workforce and East Manggarai district, especially in the data collection job seekers. Where many job seekers are difficult to list themselves as job seekers in the Department of Workers and East Manggarai Circle. This study describes how application data collection job seekers at the Department of Labor and Transmigration East Manggarai Regency, who design a new information system based sites for data capture job seekers in the solution of the problems faced by the office of the Department of Labor Aims, and emigration East Manggarai district. The collection of data obtained by conducting library research, interviews and observations. The result of this research is a web-based application searcher data capture job. Vocational training and job information for job seekers These applications can be easily accessed by anyone who wanted to gain employment as a job in East Manggarai district to win.